1972
DOI: 10.1246/bcsj.45.3031
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Water in Macromolecular Gels. IV. Proton Magnetic Resonance Studies of Water iu Macromolecular Gels

Abstract: Electrochemical and dilatometric studies have indicated that at least three states of water exist in macromolecular gels. The properties of each state of water in gels such as agarose gels were investigated by highresolution and broadline PMR over the temperature range from +50 to −60°C. The linewidth of water protons in gels was found to depend markedly on the water content of gels, and the linewidth vs. water content curve gave two inflection points. One of the inflection points can be attributed to the so-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, if the pore size is small enough, there is a possibility that a higher supersaturation is needed, due to the compartmentalization of solvents. Finally, this may also represent an effect in the diffusion of substances [69][70][71].…”
Section: Properties Of Gels Used For Crystallizationmentioning
confidence: 99%
“…However, if the pore size is small enough, there is a possibility that a higher supersaturation is needed, due to the compartmentalization of solvents. Finally, this may also represent an effect in the diffusion of substances [69][70][71].…”
Section: Properties Of Gels Used For Crystallizationmentioning
confidence: 99%
“…It has been suggested that water in natural macromolecular gels 28,29 or in synthetic hydrogels 30 can be of three types-namely, bulk water, interfacial water, and bound water, and they have been conveniently determined by techniques like dilatometry, specific conductivity, and differential scanning calorimetry. 31 For all practical purposes the three types of water have been grouped in two classes as freezable (bulk) water and nonfreezable (bound) water.…”
Section: Equilibrium Swelling Kineticsmentioning
confidence: 99%
“…According to the previous paper, the poly(NIPAAm) gels in the deswelling state above the LCST have only bound water surrounding the polymer chains, except free bulk water . Since the bound water was considered not to freeze at 253 K, the FD treatment could not cause significantly to change the structure of polymer network at Q = 1.5. From these consideration, we deduced that water content in the process of freezing gel was an important factor to control the pore size.…”
mentioning
confidence: 99%